Co-Isolation of Cytokines and Exosomes: Implications for Immunomodulation Studies - Benjamin-Davalos, Shawna; Koroleva, Marina; Allen, Cheryl L.; Ernstoff, Marc S.; Shu, Shin La (Frontiers in Immunology, 2021)
Exosomes play a vital role in intercellular communication and their immunomodulatory potential have become an important focus in cancer research. Various methods have been developed for the isolation although each method differs in the number and purity of exosomes they yield. In melanoma, tumor-derived exosomes drive immunosuppression within the tumor microenvironment. The co-elution of exosomes and soluble factors such as cytokines during isolation, however, make it difficult to ascertain the contribution of exosome cargo, as soluble cytokines are equally capable of immune suppression. In this review we will expound upon the biological relevance that exosome-associated cytokines possess. Furthermore, we discuss the technical challenges that arise during exosome isolation and what this means for further studies into the TME and in vivo work.